The effect of e-commerce on entrepreneurial decision making using an android application-based accounting information system as a moderating variable - Refangga Aditya; Dea Febriyanti (Islamic Accounting Journal, 2021)
This study aims to analyze and provide empirical evidence of the effect of e-commerce and accounting systems as moderating variables on entrepreneurial decision-making. The method used in this research is a quantitative method, with classical assumption test techniques, multiple linear regression analysis, descriptive analysis, and hypothesis testing, using SPSS version 25 software. Data were collected by distributing questionnaires using random sampling techniques distributed to 40 respondents or students. The results of the study based on the Moderated Regression Analysis (MRA) show that the presence of a moderating variable, namely the variable use of the Accounting Information System based on the android application, will be able to strengthen or increase the influence of the E-Commerce variable on the variables of Entrepreneurial Decision Making in IAIN Salatiga students.